PENGARUH KUALITAS LAYANAN, NILAI PELANGGAN TERHADAP LOYALITAS DIMEDIASI KEPUASAN PELANGGAN (STUDI PADA NASABAH SIMPANAN PT. BANK BRI CABANG PEMBANTU KARABAN PATI) - Wido Satrio, 12.05.51.0123; Marlien, R.A (Students Journal of Economic and Management, 2016)
Customer satisfaction one of BRI bank To obtain high loyalty of its customers. Customer satisfaction has a direct relationship with the quality of service and customer value. Customers whose expectations are met or even exceeded will spread positive news related to services which he felt to others. With a customer satisfied, the value of customer interest in the products and services offered by BRI bank will also increase. This is certainly very profitable for the BRI bank, because not be reached of the cost to attract new customers to retain existing customers. The aim of study is to analyze the effect of quality of service, the value of customer loyalty with customer satisfaction mediated PT. Bank BRI Branch of Pati Karaban. This research is descriptive. The total sample of 100 respondents. The research instrument used questionnaire. Analysis of data using multiple linear regression and path analysis. The results showed that service quality has positive influence on customer satisfaction. Customer value positive effect on customer satisfaction. Quality of care is a positive effect on customer loyalty. Customer value positive effect on customer loyalty. Customer satisfaction has positive effect on customer loyalty. Keywords: service quality, customer value, customer satisfaction, customer loyalty